The Public Service Staff Relations Board - Gillespie, A. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1975)
This paper is primarily an attempt to describe the organization, functions, and influence of the neutral third-party agency in the Federal Public Service collective bargaining system.